Giant bowen's disease in a paddy field worker - Divya Nair; Betsy Ambooken; Neelakandan Asokan (Wolters Kluwer Medknow Publications, 2018)
Bowen's disease (BD) is a squamous cell carcinoma (SCC) in situ with the potential for significant lateral spread. Progression to invasive SCC is rare. A 64-year-old female paddy field worker presented with a giant-sized BD on the back of the trunk. Traditional clothing (short blouse with dhoti) which exposed the back of the trunk to long hours of sunlight might explain the location of the lesion. In spite of extensive lateral spread, there were no features to suggest deeper invasion.